2007
DOI: 10.1007/s11943-007-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

Wage distributions by bargaining regime

Abstract: Collective wage bargaining, Wage structure, German Structure of Earnings Survey, Tariflohnverhandlungen, Lohnstruktur, Gehalts- und Lohnstrukturerhebung,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Two further advantages of the GSES, standing in contrast to the IAB linked employer-employee data set (LIAB; used e.g. by Dustmann et al, 2009), are that hours of work are reported and that earnings are neither truncated nor censored (Kohn and Lembcke, 2007;Fitzenberger and Reize, 2002). Moreover, even though the sampling design asks firms to provide data only on a fraction of their workforce, many firms in 2006 prefer to supply data on all employees.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two further advantages of the GSES, standing in contrast to the IAB linked employer-employee data set (LIAB; used e.g. by Dustmann et al, 2009), are that hours of work are reported and that earnings are neither truncated nor censored (Kohn and Lembcke, 2007;Fitzenberger and Reize, 2002). Moreover, even though the sampling design asks firms to provide data only on a fraction of their workforce, many firms in 2006 prefer to supply data on all employees.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
“…Given the heterogeneity in wage trends between West and East Germany, (see e.g. Kohn and Lembcke, 2007;Gernandt and Pfeiffer, 2007;Orlowski and Riphahn, 2009), we restrict our analysis to West Germany. The GSES provides precise information on whether an employee is covered by one of the collective bargaining regimes, i.e.…”
Section: Data and Descriptive Statisticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Da hohe Lohnansprüche häufig mit genau solchen Argumenten legitimiert werden, sollte der Einfluss auf hohe Löhne größer sein als im unteren Bereich der Lohnverteilung. Durch die zunehmende Verbreitung von Bonuszahlungen am oberen Ende der Lohnverteilung wird dieses Argumentationsmuster zunehmend wichtiger(Lemieux, MacLeod & Parent, 2009; für Deutschland: Sommerfeld, 2013) -gerade in Betrieben ohne Tarifbindung. Beim Frauenanteil im Management kommt hinzu, dass es Frauen auf Ebenen unter dem Management aufgrund des reduzierten homosozialen Rekrutierungsverhaltens von Männern leichter fallen sollte, in höhere Positionen zu gelangen, sodass auch hier zu erwarten ist, dass der Effekt im oberen Teil der Lohnverteilung stärker ausfällt.…”
unclassified